Survey of antibacterial activity and release kinetics of gold-decorated magnetic nanoparticles of Fe0 conjugated with sulfamethoxazole against Escherichia coli and Staphylococcus aureus. (October 2022) - Shi, Nan; Wang, Haibin; Cui, Chengjun; Afshar, Elham Ashrafzadeh; Mehrabi, Fatemeh; Taher, Mohammad Ali; Shojaei, Moein; Hamidi, Ashraf Sadat; Dong, Yu
Abstract: Drug delivery of antibiotics with magnetic nanoparticles improved by coating metals such as gold and silver has recently been studied. This work describe a simple method to synthesize modified magnetic nanoparticles which have high ability to modify the customary formulation of antibiotics such as sulfamethoxazole (SMX) and pursuant study of adsorption-desorption (release) of this drug. These synthesized nanoparticles were characterized by different methods, including field emission scanning electron microscopy, energy dispersive X-ray spectroscopy and mapping, Fourier-transform infrared spectroscopy, X-ray diffraction, vibrating-sample magnetometry, thermogravimetric analysis and zeta potential test. Present assay showed a well correlation with the introduced carrier for the drug. Also the hypothesis were proved by some adsorption isotherm models and drug kinetics studies of carriers with different drug release kinetics models. This study confirmed the adsorption isotherm models and kinetics of drug sorbate are Temkin and Pseudo-First-Order Lagergren models, respectively; the kinetics of drug release from this carrier is based on Zero-Order model. The values of MIC in antibacterial test for pure SMX and SMX conjugated nanoparticles against Escherichia coli were calculated to be 14 and 2.5 μg/mL, respectively, and these values against Staphylococcus aureus were 24 and 1.25 μg/mL, respectively. Graphical abstract: Image 1 Highlights: The gold-decorated of Fe3 O4 NPs attached to sulfamethoxazole for the first time. The NPs attached to sulfamethoxazole was characterized by different techniques. The results showed significant reduction in dosage of sulfamethoxazole. It can be an appropriate method to overcome the problem of microbial resistance.